Addressing the quality of paediatric primary care: health worker and caregiver perspectives from a process evaluation of PACK child, a health systems intervention in South Africa - Robyn Curran; Jamie Murdoch; Max Bachmann; Eric Bateman; Ruth Cornick; Sandra Picken; Makhosazana Lungile Simelane; Lara Fairall (BMC, 2021)
Abstract Background The WHO's Integrated Management of Childhood Illness (IMCI) has resulted in progress in addressing infant and child mortality. However, unmet needs of children continue to present a burden upon primary healthcare services. The capacity of services and quality of care offered require greater support to address these needs by extending and integrating curative and preventive care for the child with a long-term health condition and the child older than 5, not prioritised in IMCI. In response to these needs, the PACK Child intervention was developed and piloted in October 2017-February 2019 in the Western Cape Province of South Africa. We report health worker and caregiver perspectives of the existing paediatric primary care context as well as the extent to which PACK Child functions to address perceived problems within the current local healthcare system. Methods This process evaluation involved 52 individual interviews with caregivers, 10 focus group discussions with health workers, 3 individual interviews with trainers, and 31 training observations. Interviews and focus groups explored participants' experiences of paediatric primary care, perspectives of the PACK Child intervention, and tensions with implementation in each context. Inductive thematic analysis was used to analyse verbatim interview and discussion transcripts. Results Perspectives of caregivers and health workers suggest an institutionalised focus of paediatric primary care to treating children's symptoms as acute episodic conditions. Health workers' reports imply that this focus is perpetuated by interactions between contextual features such as, IMCI policy, documentation-driven consultations, overcrowded clinics and verticalised care. Whilst these contextual conditions constrained health workers' ability to translate skills developed within PACK Child training into practice, the intervention initiated expanded care of children 0-13 years and those with long-term health conditions, enhanced professional competence, improved teamwork and referrals, streamlined triaging, and facilitated probing for psychosocial risk. Conclusion PACK Child appears to be catalysing paediatric primary care to address the broader needs of children, including long-term health conditions and the identification of psychosocial problems. However, to maximise this requires primary care to re-orientate from risk minimisation on the day of attendance towards a view of the child beyond the day of presentation at clinics.